IMPLEMENTATION OF PT KERTA GAYA PUSAKA PACKAGE DELIVERY RECEIPT NUMBER TRACKING GIS IN ASAHAN - AKMAL HUDHA TANJUNG; Muhammad Amin; Santoso Santoso (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
Geographic Information System (GIS) is a system that presents information in graphical form using a map as an interface, in addition to that geographic information system also has the ability to connect various data at a certain point. By applying Geographic Information System (GIS) at PT. Kerta Gaya Pusaka can make it easier for couriers in the package delivery process because the address search process becomes more accurate which can bring up information to the courier, namely receipt number, sender name, recipient name, sender's home address, recipient, weight and shipping costs and this system can accessed by the sender and receiver to determine the status of the existence of the packet